Serum Albumin Levels as a Potential Marker for the Predictive and Prognostic Factor in Sudden Sensorineural Hearing Loss: A Prospective Cohort Study - Zheng, Zhong; Liu, Chengqi; Shen, Ying; Xia, Liang; Xiao, Lili; Sun, Yuanyuan; Wang, Hui; Chen, Zhengnong; Wu, Yaqin; Shi, Haibo; Feng, Yanmei; Yin, Shankai (Frontiers in Neurology, 2021)
Objectives: As a common otology emergency, sudden sensorineural hearing loss (SSNHL) has a great impact on quality of life. The diagnosis and treatment of SSNHL remain challenging. This study aims to identify and investigate the association of liver functions with SSNHL. Methods: A total of 135 SSNHL patients and 135 sex- and age- matched controls were prospectively enrolled. The baseline and clinical characteristics, along with liver function levels of participators were collected. Linear correlation, logistic regression, and receiving operator characteristics curve analysis tests were applied to examine the association between liver functions levels and SSNHL. Results: There were no differences in baseline characteristics between SSNHL and control groups. The albumin (ALB) level of SSNHL group were significantly lower than those in the control group (P < 0.001). The logistic regression showed that the low ALB level may be a predictive factor of SSNHL with adjusted ORs of 0.809 (95% CI, 0.742-0.882, P < 0.001). By comparing the indicators of different prognosis groups, we found that the effective group had significantly lower hearing impair onset and higher ALB (P = 0.001), AGR (P = 0.003) levels than the ineffective group. Logistic regression revealed that hearing level onset (OR, 0.976; 95% CI, 0.956-0.997; P = 0.026) and ALB level (OR, 1.181; 95% CI, 1.071-1.301; P = 0.001) showed strong associations with treatment outcome. Conclusions: Lower ALB levels, within the normal ranges, were associated with the occurrence and unfavorable outcome of SSNHL. However, further research on the underlying mechanisms needs to be conducted.